Relasi Organisasi Non Pemerintah - Partai Politik dalam Penguatan Partisipasi Publik di Kota Malang - Budhy Prianto (Universitas Riau, 2010)
The objectives of this research is to find out the relation between NGOs and politicalparty in strengthening the public participation in Malang City. The research sample taken purpo-sively from 18 functional NGOs and 8 political parties which have representative in DPRD MalangCity. The data is taken from interview and documentary, and analyzed qualitative descriptively. Theresearch conducted in two stages. The first stage of this research is to identify and classify NGOsinto three categories, namely, developmentalist (parastatal), liberal reformist (professional), andtransformatorist (progressive). Meanwhile, the political party is identified and classified based onfive typological political parties, they are: clientelist linkages, encapsulating linkages, program-matic linkages, personalistic linkages and charismatic bonds, and marketing linkages. The NGOswhich has liberal reformation (professional) type because of its idealism and moderat character-istics has the most possibility to make relationship with other political party, meanwhile from thepolitical party side which has the most possibility to make relationship with NGOs is the politicalparty which has encapsulating linkages type, this happens because the political party with thistype has more transparancy ideology and identity, also more loyal cadres and constituent basic.